Стилист: роман / Александра Маринина - Маринина Александра Борисовна (Вече, 1997)
Экземпляры: ф.7 (1997) / Инвентарный номер: 40001 / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44